Marshall On Consumers' Surplus in International Trade - Young, Allyn A. (Quarterly Journal of Economics, 1924)
Journal Article Marshall on Consumers' Surplus in International Trade Get access Allyn A. Young Allyn A. Young Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 39, Issue 1, November 1924, Pages 144–150, https://doi.org/10.2307/1883959 Published: 01 November 1924